The Impact of Cyberbullying on Self-Harming Behavior and Suicidal Thoughts among Adolescents: A Meta-Analysis - Amalia Khurotul Mahzunah; Ica Yuniar Sari; Berti Vega Paradela; Bhisma Murti; Elsa Tursina (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Online bullying often occurs among teenagers. This is an important risk factor for self-injurious behavior and suicidal ideation. This study aimed to analyze and estimate the magnitude of the effect of online bullying on self-injurious behavior and suicidal ideation in adolescents. Subjects and Method: This research is a systematic review and meta-analysis using the PICO model. Population: Adolescents, Intervention: Online bullying, Comparison: No online bullying, Outcome: Self-injurious behavior and suicidal ideation. The research data used was obtained through Google Scholar, Science Direct, BMC Public Health, and Scopus with the keywords (“Cyberbullying”) AND (“Self-harm”) AND (“Suicidal Ideation”) AND (“Mental Health”) AND (“Cross-sectional”). Inclusion criteria were cross-sectional articles in English published from 2014 to 2024. Data analysis was carried out using the Review Manager 5.3 application. Results: Meta-analysis was conducted on 8 primary studies with outcomes for self-harm behavior and 9 primary studies with outcomes for suicidal ideation. These primary studies come from Singapore, Vietnam, Taiwan, China, South Korea, Iran, Australia and America. The sample size was 47,708 adolescents for self-injurious behavior outcomes and 63,173 adolescents for suicidal ideation outcomes. Adolescents with online bullying are 3.64 times more likely to have self-injurious behavior (aOR= 3.64; 95% CI= 3.14 to 4.22; p<0.001) and 2.64 times more likely to have suicidal ideation (aOR= 2.64; 95% CI= 1.94 to 3.60; p<0.001) compared to adolescents without online bullying. The funnel plot indicates the existence of publication bias which tends to reduce the true effect (underestimate) on the outcome of suicidal ideation. Conclusion: Online bullying statistically significantly increases the risk of self-injurious behavior and suicidal ideation in adolescents.